2008
DOI: 10.29309/tpmj/2008.15.04.2926
|View full text |Cite
|
Sign up to set email alerts
|

Appendectomy;

Abstract: . Objective: The purpose of this prospective study was to compare length of hospital stay, in hospital complications andoperative time between laparoscopic appendectomy (LA) and open appendectomy (OA). Setting: This prospective study was carried out atKing Khalid Hospital, Najran, Kingdom of Saudi Arabia over a period of 26 months from July 2002 to August 2004. Methods: Patients wererandomly divided into laparoscopic and open appendectomy groups and length of stay, operative time and in hospital complications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Similar results were shown by Tariq w.k.a. The most common presentation of patients with obstructive jaundice was female, with a mean age of 49 years (Khanzada et al, 2008). In contrast to our study, Gupta AK at EL showed that the most common gender presented with obstructive jaundice was male (Gupta et al, 2017).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Similar results were shown by Tariq w.k.a. The most common presentation of patients with obstructive jaundice was female, with a mean age of 49 years (Khanzada et al, 2008). In contrast to our study, Gupta AK at EL showed that the most common gender presented with obstructive jaundice was male (Gupta et al, 2017).…”
Section: Discussioncontrasting
confidence: 99%
“…Similar results were seen in Umeshchandra et al and Tariq w k at el. (Khanzada et al, 2008;Umeshchandra and Maitra, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Thyroidectomy, either lobectomy or total thyroidectomy, is the gold standard treatment depending upon the diagnosis. 4 The known complications include recurrent laryngeal nerve paralysis, dysphagia, dysphonia, seroma, compressive hematoma, and hypoparathyroidism. 2 5…”
Section: Introductionmentioning
confidence: 99%
“…After the introduction of T. Kocher's meticulous surgical technique in the beginning of 20 th century, the progression in the development of safer general anesthesia techniques, the development of fine hemostatic instruments and better antiseptic means and measures, thyroidectomy has evolved into a surgical procedure with low morbidity and mortality rates. 4 5 6 The frequency of thyroidectomy has increased secondary to the increase in prevalence of thyroid carcinoma globally. 2 Previously, a 10.7% morbidity rate was reported after thyroidectomy but, according to Lombardi et al, the mortality rate has gone down to essentially 0% and morbidity rates have declined to 3%; 5 whereas the mortality rate after thyroid lobectomy according to British association of endocrine and thyroid surgeons (BAETS) is 0.2%, majorly secondary to hematoma.…”
Section: Introductionmentioning
confidence: 99%